La perspectiva local-global en el medio rural ecuatoriano - Martínez Valle, Luciano (2006)
This article explores the local-global relation in the rural society based on the local development theories. In the first moment a critic of a traditional concept of development like as economic growth is achieved; then, the dynamic of the local workers in the globalized social space is recuperated as well as theirs economics possibilities of successful binding. In this way, some local experiences of development in the Ecuadorian case are analyzed in comparative method with the Italian successful experience.